Investigation Group Learning Models On Social Sciences Learning - Wardoyo, W A U; Sumilat, J M (Journal of Educational Method and Technology, 2019)
The purpose of this study is to improve learning outcomes of natural resources material in social sciences  subjects. This study uses a classroom action research method with four stages, namely planning, action, observation, and reflection. Data collection on learning outcomes is obtained through tests. Data analysis was done by calculating the percentage of completeness of learning, and research was said to be successful if the completeness of learning outcomes was 85%. The results of the study in the first cycle showed that Social sciences  learning outcomes reached 68.85% and after the implementation of improved learning in the second cycle learning outcomes increased to 88.84%. This study concluded that the application of the investigation group model can improve student learning outcomes in social sciences  learning.Keywords: Group Investigation Learning Model, Social sciences  Learning Outcomes